Association of computed tomography‐derived muscle mass and quality with delayed acquisition independent walking after cardiovascular surgery - Kazuya Shimizu; Ryota Matsuzawa; Shinya Nakamura; Keita Murakawa; Hideo Kawakami; Masaki Tabuchi; Motoaki Ohnaka; Masamichi Matsumori; Akira Tamaki (Wiley, 2024)
Abstract Background In the context of cardiovascular surgery, the foremost concern lies in delayed functional recovery, as typified by the acquisition of independent walking after surgery, among older patients with decline in skeletal muscle mass and quality. Computed tomography (CT), which is typically employed for the preoperative assessment of pathological conditions in patients undergoing cardiovascular surgery, is also suitable for screening for potential decline in skeletal muscle mass and quality. The aim of this study was to examine the predictive capabilities of CT‐derived parameters such as muscle mass and muscle quality for the delayed acquisition of independent walking in the postoperative period. Methods This retrospective study enrolled consecutive Japanese patients who underwent elective cardiovascular surgery between May 2020 and January 2023. In total, 139 patients were included in the analyses. Based on the preoperative CT image, the psoas muscle volume index (PMVI) and psoas muscle attenuation (PMA) were calculated. Information on patient characteristics, including preoperative physical fitness such as handgrip strength/body mass index (GS/BMI), short physical performance battery (SPPB), and 6‐min walking distance (6MWD), were obtained from the medical records. We defined delayed acquisition of independent walking after surgery as the inability to walk 100 m within 4 days after surgery. Results The median age of the patients was 72 (interquartile: 64-78) years, and 74.8% (104/139) were men; 47.5% corresponded to the delayed group. The areas under the curves of SPPB, GS/BMI, 6MWD, PMVI, and PMA against delayed acquisition of independent walking after surgery were 0.68 [95% confidence interval (CI): 0.59 to 0.77], 0.72 (95% CI: 0.63 to 0.80), 0.73 (95% CI: 0.65 to 0.82), 0.69 (95% CI: 0.60 to 0.78), and 0.78 (95% CI: 0.70 to 0.85), respectively. In the multivariate logistic regression analysis, low PMA was significantly associated with delayed acquisition of independent walking even after adjustment for patient characteristics including physical fitness [model 1: SPPB (OR, 1.14; 95% CI: 1.03-1.25), model 2: GS/BMI (OR, 1.13; 95% CI: 1.03-1.25), and model 3: 6MWD (OR, 1.14; 95% CI: 1.03-1.25)], but PMVI was not. Conclusions Our study revealed a strong association between PMA, a marker of CT‐derived muscle quality, and the postoperative delay in achieving independent walking in patients who underwent cardiovascular surgery. The technique to obtain information on muscle quality during the time period before surgery may be an option for timely therapeutic intervention in patients who may have delayed acquisition of independent walking after surgery.